Prevalence and prognostic value of MYD88 and CD79B mutations in ocular adnexal large B-cell lymphoma: a reclassification of ocular adnexal large B-cell lymphoma. Issue 4 (27th October 2021) - Kirkegaard, Marina Knudsen; Minderman, Marthe; Sjö, Lene Dissing; Pals, Steven T; Eriksen, Patrick R G; Heegaard, Steffen
Abstract : Aims: To (1) reclassify ocular adnexal large B-cell lymphomas (OA-LBCLs) per 2016 WHO lymphoma classification and (2) determine the prevalence of MYD88 and CD79B mutations and their association with clinical parameters among OA-LBCLs. Methods: This study is a retrospective analysis of all OA-LBCLs diagnosed in Denmark between 1980 and 2018. Medical records and tissue samples were retrieved. Thirty-four OA-LBCLs were included. Fluorescence in situ hybridisation and Epstein-Barr-encoded RNA in situ hybridisation were used for the reclassification. Mutational status was established by allele-specific PCR and confirmed by Sanger sequencing. Primary endpoints were overall survival, disease-specific survival (DSS) and progression-free survival (PFS). Results: Two LBCL subtypes were identified: diffuse large B-cell lymphoma (DLBCL) (27 of 32; 84%) and high-grade B-cell lymphoma (HGBL) with MYC and BCL2 and/or BCL6 rearrangements (5 of 32; 16%). cMYC/BCL2 double-expressor DLBCLs had a poorer DSS than non-double-expressor DLBCLs (5-year DSS, 25% vs 78%) (HR 0.23; 95% CI 0.06 to 0.85; p=0.014). MYD88 mutations were present in 10 (29%) of 34 lymphomas and carried a poorer PFS than wild-type cases (5-year PFS, 0% vs 43%) (HR 0.78; 95% CI 0.61 to 0.98; p=0.039). CD79B mutations were present in 3 (9%) of 34 cases. Conclusion: OA-LBCL consists mainly of two subtypes: DLBCL and HGBL with MYC and BCL2 and/or BCL6 rearrangements. MYD88 mutations are important drivers of OA-LBCL. MYD88 mutations, as well as cMYC/BCL2 double-expressor DLBCL, appear to be associated with a poor prognosis. Implementing MYD88 mutational analysis in routine diagnostics may improve OA-LBCL prognostication.